Tutorial Education Program a group of self-reflection in initial formation - Renata Caroline Dias Machado; Graciela Paz Meggiolaro; Roque Ismael da Costa Güllich (Universidade Federal do Oeste da Bahia, 2020)
Teacher training in Brazil has assumed the Research-Action trend since the early 2000s. Thus, we aim to understand the role of reflection in the Action-Research process as a way for learning during the experiences of initial Formation of Science teachers. In this way, we analyzed and categorized, through thematic content analysis, the Formation diary of undergraduates in the area of Sciences, participants in the Tutorial Education Program (PETCiências). The analysis categories were defined following three thematic axes: i) levels of reflection, ii) types of reflection and iii) content of reflection. In the study, we highlighted the role of the Formation diary in the initial Formation, bringing opportunities to subjects who reflect on themselves through the Research-Formation-Action process, which is a construction that takes place in the collective that helps in critical, self-reflective development and adds quality to development. teaching professional.